2004
DOI: 10.1111/j.1939-1676.2004.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Absorption of Amitriptyline and Buspirone after Oral and Transdermal Administration to Healthy Cats

Abstract: A prospective study was performed to determine the relative availability of buspirone and amitriptyline after oral and transdermal routes of administration in 6 adult cats. For topical administration, drugs were compounded in a transdermal organogel containing pluronic and lecithin (PLO). Using a crossover design, each cat received a single dose of amitriptyline (5 mg) and buspirone (2.5 mg) by the transdermal and oral route of administration with at least a 2-week washout interval between drug treatments. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 10 publications
(9 reference statements)
0
19
0
Order By: Relevance
“…Because of this, many compounding pharmacies have started formulating drugs into gels, which are applied to the inner side of the cat's ear and are thought to be absorbed through the skin for systemic action. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Not all drugs are suitable for transdermal penetration and only a few drugs have been studied in cats to determine whether they reach therapeutic concentrations after absorption by this route. [21][22][23]26,27,30,31 There are several factors that affect the transdermal delivery of drugs.…”
mentioning
confidence: 99%
“…Because of this, many compounding pharmacies have started formulating drugs into gels, which are applied to the inner side of the cat's ear and are thought to be absorbed through the skin for systemic action. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Not all drugs are suitable for transdermal penetration and only a few drugs have been studied in cats to determine whether they reach therapeutic concentrations after absorption by this route. [21][22][23]26,27,30,31 There are several factors that affect the transdermal delivery of drugs.…”
mentioning
confidence: 99%
“…31,32 In the most recent study, 31 the authors showed that transdermal methimazole was not as effective as oral methimazole for treating hyperthyroid cats, but it may be an option for some cats that are difficult to medicate orally. Amitriptyline and buspirone administered transdermally to cats 33 showed negligible transdermal absorption. When dexamethasone was topically administered in PLO, there was negligible absorption in cats.…”
Section: Transdermal Drugsmentioning
confidence: 94%
“…In veterinary medicine, there are studies on transdermal absorption of different active substances such as fluoxetine (Ciribassi et al 2003), fentanyl, morphine (Krotscheck et al 2004), dexamethasone (Willis-Goulet et al 2003), buspirone, amitryptylene (Mealey et al 2004), glypizide (Bennett et al 2005), and methimazole (Hoffmann et al 2003).…”
Section: (Received 30 October 2007; Accepted 16 January 2008)mentioning
confidence: 99%